Three-dimensional mesh registration for localization of body anatomy - Ping, Guiju (2018)
Developed a system to locate massage points on a human. This system is developed using ROS (Robot Operating System), targeted to use in massage robot to help the robot to locate the suitable massage points on the patient and avoid bones. The system requires a Realsense Camera to capture the point cloud and image of the patient. Users can select the target region by drawing a rectangle on User Interface. The system provided hsv filter function to help users to locate the key points of the patients. Locating of massage points are done through 3D non-rigid registration. This project increased the efficiency and safety of the massage robot.